Prevalence of impacted teeth and pattern of third molar impaction among Kerala population a cross sectional study - Sajjad Salam; Ashitha Bary; Aatif Sayed (Wolters Kluwer Medknow Publications, 2023)
Background: When a tooth does not erupt to the normal functional position, the tooth is said to be impacted. Impaction can be partial or complete which has many problems associated with it and adjacent tooth. Aim: To assess the prevalence of impaction and pattern of mandibular impaction among adults in Ernakulum district, Kerala. Methodology: Retrospective data were analyzed using panoramic radiographs of 1,500 subjects were correlated with demographic details age and gender. Two independent investigators carried out the research independently. Data were analyzed using SPSS. Results: The prevalence of teeth impaction was 22.0%. A total of 330 subjects presented with at least one impacted tooth. Mandibular third molars were the most commonly impacted tooth (17.46%). The mesioangular orientation was the most common pattern. There was no gender difference in prevalence of impaction (P >.05). Conclusion: Twenty two percent among Kerala population. The mandibular wisdom teeth were the most commonly impacted teeth. Mesioangular orientation was the most common pattern. No association was found between impacted teeth as per gender.